Sources of income inequality: A comparison of Japan and the United States - Toshiaki Aizawa; Robert Dekle; Matthias Helble (Asian Development Bank Institute (ADBI), 2017)
This paper compares the sources of income inequality in Japan and the United States. We exploit two longitudinal household surveys to decompose the income inequality in both countries. For Japan, we use Keio Household Panel Survey data and the five latest waves (2009-2013). For the United States, the data comes from the Panel Study of Income Dynamics and covers the years 2009, 2011, and 2013. To ensure comparability between the two countries, we restrict our sample to household heads between 35 and 65 years old and currently working. In a first step, we calculate the Gini coefficient of labor income for the two samples. We find that the Gini coefficient of labor income is higher in the United States (0.453) than in Japan (0.329), corroborating well-established previous findings. In a second step, we decompose the income inequality in both countries by using a comparable set of variables. Our results show that differences in the number of years of education and marital status explain the largest part of income inequality in Japan. In the United States, education and working hours are the strongest contributors to unequal income distribution. Finally, when introducing additional, country-specific variables, we find that working for a large company and being an irregular worker are important drivers of inequality in Japan. For the United States, lower wages for African Americans appears to contribute 5%-10% to income inequality.
Keywords: D33; O51; O53; 330; Economics; Poverty; Japan